Dynamics and morphological limitation of intracohort cannibalism during the early life stages of captive barred sorubim Pseudoplatystoma reticulatum - Ribeiro, Flavio F. [UNESP]; Portella, Maria C. [UNESP] (Elsevier, 2021)
The present study investigated the biological basis of cannibalism in Pseudoplatystoma reticulatum. Newly-hatched P. reticulatum were reared under a standard rearing protocol up to 50 days after hatching (DAH). Fish samples were periodically collected to construct a predictive model of the morphological limits of cannibalism. This model was further validated by the outcomes of a pairwise predation trial where cannibals were challenged with different prey sizes. Replicated small-scale cultures were carried-out in parallel to assess the ontogeny and dynamics of cannibalism. The predictive model showed that P. reticulatum cannibals are able to ingest prey from 77 to 85% of their own size. All ingested prey during the pairwise predation trial remained below the maximum prey size estimated by the predictive model, indicating model reliability. Three types of mortalities were distinguished during the early life stages of P. reticulatum: mortality owing to causes other than cannibalism (OM), incomplete cannibalism (ICM, half-ingested fish), and complete cannibalism (CCM, missing fish), each one impacting the population at different stages. By 50 DAH, survival was 21.32 ± 1.50% of the initial population, with the three types of mortalities impacting the population at similar levels (P > 0.05). The outcomes of this study progress our understanding of the biological basis of cannibalism and contribute towards advancing the rearing technologies of native fish species in South America.
Keywords: Cannibalistic dynamics; Fish larvae; Intraspecific predation; Piscivory; Predatory behavior